Numerical Based Approach for Predicting the Response of Flexible Risers Under Oscillatory Flows at Low Re and KC Numbers - Valencia-Cardenas, Maria Catalina; Riveros-Jerez, Carlos Alberto (Scientia et Technica, 2019)
Flexible riser response prediction relies on semi-empirical models hindered by limitations due experimental data scarcity for particular modelling considerations. This paper presents a numerical-based approach for predicting the flexible riser response under oscillatory flows. A single freedom degree spring-mass-damper system is employed with the mass allowed to move in cross-flow direction. To discretize the Navier-Stokes equations the Finite Volume Method is used. To analyse the flow patterns in each regime the cylinder oscillating period is executed for long time. A bi-dimensional model is setting up using OpenFOAM simulations. Flow behavior, hydrodynamic forces and frequencies were analyzed for Reynolds values between 40-1000 using a KC number 7,9. For Reynolds less than 300 the behavior is in agreement with the literature. For Reynolds 300 or higher, some discrepancies appear in the system dynamics. The numerical results obtained from the numerical approach shows good agreement with experimental data collected from a flexible riser model.